(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article analyzes the areas of application of artificial intelligence and digital technologies in the pharmaceutical industry, their impact on research, production and practical pharmacy processes. In particular, the identification of drug molecules, optimization of clinical trials, improvement of the pharmacovigilance system, and the effectiveness of electronic prescription and digital management mechanisms are studied. Based on the analysis, the importance of artificial intelligence technologies in reducing time, cost and errors associated with the human factor is revealed. Also, scientifically based recommendations are given on existing problems in the industry, in particular, issues related to data security and personnel qualifications.